2008
DOI: 10.1074/jbc.m709693200
|View full text |Cite
|
Sign up to set email alerts
|

Redox-independent Activation of NF-κB by Pseudomonas aeruginosa Pyocyanin in a Cystic Fibrosis Airway Epithelial Cell Line

Abstract: The roles of the Pseudomonas aeruginosa-derived pigment pyocyanin (PYO) as an oxidant and activator of the proinflammatory transcription factor NF-B were tested in a cystic fibrosis (CF) airway epithelial cell line, CF15. 100 M PYO on its own had no effect or only small effects to activate NF-B (<1.5-fold), but PYO synergized with the TLR5 agonist flagellin. Flagellin activated NF-B 4 -20-fold, and PYO increased these activations >2. Pseudomonas aeruginosa is commonly present in lungs of cystic fibrosis (CF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Bacterial antigens, such as pili, flagella, DNA, and quorumsensing autoinducer molecules (137,151), are detected by the host and induce release of proinflammatory factors such as interleukin-8 (IL-8), tumor necrosis factor alpha (TNF-␣), IL-1, IL-6, complement chemoattractants, and leukotriene B 4 (61, 133,492,651). The bacteria themselves are not merely passive bystanders in this process; rather, P. aeruginosa has the potential to synthesize factors that damage host cells, augmenting release of proinflammatory factors (535). For example, P. aeruginosa proteolytic enzymes alter host iron-containing proteins in a way that favors hydroxyl radical formation, which contributes to host tissue injury and inflammation (70).…”
Section: Pathogenesis Of Pulmonary Decline In Cfmentioning
confidence: 99%
“…Bacterial antigens, such as pili, flagella, DNA, and quorumsensing autoinducer molecules (137,151), are detected by the host and induce release of proinflammatory factors such as interleukin-8 (IL-8), tumor necrosis factor alpha (TNF-␣), IL-1, IL-6, complement chemoattractants, and leukotriene B 4 (61, 133,492,651). The bacteria themselves are not merely passive bystanders in this process; rather, P. aeruginosa has the potential to synthesize factors that damage host cells, augmenting release of proinflammatory factors (535). For example, P. aeruginosa proteolytic enzymes alter host iron-containing proteins in a way that favors hydroxyl radical formation, which contributes to host tissue injury and inflammation (70).…”
Section: Pathogenesis Of Pulmonary Decline In Cfmentioning
confidence: 99%
“…However, with increase in wound healing time point, loss of viability of P.aeruginosa, and inactivation of its virulent factors possibly led to significant down regulation of NF-kB and inflammatory cytokines. It has been shown that virulent factors secreted by P.aeruginosa such as LPS, phospholipase, proteolytic enzymes and pyocyanin induce damage to fibroblast, endothelial cells in the wound milieu and delay the wound healing [4][5][6]31) . Also, a prolonged inflammatory phase induced by infection, causes increased levels of proteases which destroy components of the extracellular matrix and damage the growth factors 31) .…”
Section: Original Articlesmentioning
confidence: 99%
“…Management of infections caused by P. aeruginosa is difficult due to the rapid emergence of multi-antibiotic resistant strains. Further, the toxins and cell components of these bacteria such as lipopolysaccharide (LPS) can induce overproduction of local proinflammatory mediators, casue cell death [3][4][5][6][7][8][9] . Proteases produced by these bacteria also degrade host matrix proteins, thereby impairing host tissue integrity [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Treatments with agonists were made by diluting stock solutions into Ringer solution at the concentrations stated in the text. Fluorescence ratio imaging measurements of Ca cyto were performed using equipment as described above and methods reported previously (46,47). Emission (Ͼ510 nm) images were collected during alternate excitation at 350 Ϯ 5 and 380 Ϯ 5 nm.…”
Section: Q-pcr Analysis Of Mouse Bax and Bak And Mouse Andmentioning
confidence: 99%